2007
DOI: 10.1002/marc.200700186
|View full text |Cite
|
Sign up to set email alerts
|

Organic Memory Device Based on Carbazole‐Substituted Cellulose

Abstract: A novel functionalized cellulose derivative, 6‐O‐[4‐(9H‐carbazol‐9‐yl)butyl]‐2,3‐di‐O‐methyl cellulose, has been synthesized and characterized. The photoluminescence spectrum of the as‐cast film of the cellulose derivative exhibits sharp peaks with a well‐defined vibronic structure, which indicates that the interaction between carbazole groups is rather weak. This is in contrast to the broad spectrum of a poly(N‐vinylcarbazole) thin film. A thin‐film device, where the cellulose derivative is sandwiched by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Besides their traditional applications as additives in the food industry, in coatings, printing, cosmetic, textile, and in the pharmaceuticals industry, new cellulose derivatives have also been investigated for their applications, such as drug delivery systems [140], in chiral separation and recognition [141], as photoactive materials [142], as antioxidant agents [143], in memory of electronic devices [144], and graft copolymers [145].…”
Section: Industrial Cellulose Derivative Production Methodsmentioning
confidence: 99%
“…Besides their traditional applications as additives in the food industry, in coatings, printing, cosmetic, textile, and in the pharmaceuticals industry, new cellulose derivatives have also been investigated for their applications, such as drug delivery systems [140], in chiral separation and recognition [141], as photoactive materials [142], as antioxidant agents [143], in memory of electronic devices [144], and graft copolymers [145].…”
Section: Industrial Cellulose Derivative Production Methodsmentioning
confidence: 99%
“…[25] Zhang et al have homogeneously synthesised carbazole-substituted hydroxyethyl cellulose (HEC) where, by increasing the cellulose degree of substitution with carbazole, the fluorescence lifetime was increased. [26] The…”
Section: Introductionmentioning
confidence: 99%
“…[151][152][153] Natural biomaterials, especially proteins, open up new opportunities for resistive-switching memory devices by endowing them with outstanding properties, such as mechanical fl exibility, biocompatibility, and light-weight, which renders them suitable for applications in biocompatible data-storage devices and biointegrated electronics. [ 32,[159][160][161][162][163][164] Silk protein exhibits more appealing properties compared with other biocompatible materials, such as ferritin, [ 159 ] cellulose, [ 165 ] and DNA, [ 166,167 ] for resistive-switching memory applications duo to its advantageous properties, such as mechanical robustness, fl exibility in thin-fi lm form, optical transparency, and compatibility with aqueous processing. [ 32,168 ] Silk-fi broin fi lms exhibited bipolar memristive switching behavior in a device with an indium tin oxide (ITO)/ fi broin/Al sandwich structure, with an OFF/ON ratio of 10 and retention time of 10 3 s. [ 78 ] The resistive switching of the above memristor was further studied at the microscopic scale, [ 169 ] which revealed that the current conduction process is dominated by fi lamentary conduction during LRS, and trap-assisted current conduction when in the HRS.…”
Section: Resistive-switching Memory Devicesmentioning
confidence: 99%